Meaning in life, parental monitoring, perceived parental support and family relationship among adolescents in Malaysia - Yeo, Agnes Zhan Xuan (2023)
Creating meaning in life throughout adolescence imply to be crucial to increasing the likelihood of these benefits in the future. This study intends to examine the relationship between meaning in life, parental monitoring, perceived parental support, and family relationship in Malaysia. This research has utilized a quantitative cross-sectional correlational research approach. The findings for this study were gathered using online Google Forms from a total of 204 respondents through purposive sampling. The respondents were only 18 and 19-year-old Malaysian students (M = 18.67 years; SD = 0.471 years). Chinese respondents (n = 187, 91.67%) were more than Malay (n = 8, 3.92%) and Indian (n = 9, 4.41%) respondents. The measurements used were the Meaning in Life Questionnaire (MLQ), Parental Monitoring Assessment (PMA), Perceived Parental Support (PPS) Scale, and Family Relations/Cohesion Scale (FRCS). The outcomes proposed that meaning in life was strongly and favourably related to parental monitoring, perceived parental support, and family relationship. Meanwhile, it was discovered that family relationships were not a significant predator of meaning in life, but parental monitoring and perceived parental support were. These findings may act as a guideline to researchers, mental health practitioners, educational institutions, parents, and the community to cultivate a healthy and supportive monitoring environment for the adolescents in their pursuit of meaning in life in Malaysia.